Economic benefits of FAD set limits throughout the supply chain. (May 2019) - Holmes, Glen; Hanich, Quentin; Soboil, Mark
Abstract: Fish aggregating devices (FADs) have over recent decades, become an integral tool in commercial tuna fisheries due to their increased efficiency over free school catches. Technological development has further aided in their increased usage and reliance by many fleets. The negative consequences of FADs include higher rates of non-target species such as juvenile bigeye and yellowfin tunas. Management of this negative consequence has to date been undertaken by spatial and/or temporal closures to fishing. These closures can result in an economic burden to fishermen via reduced catch rates, coastal states trying to sell access rights to fishing grounds at the same rate with no closure in place, and canneries through variability in supply and subsequent volatility in market prices. This paper examines the economic benefits of replacing closures with FAD set limits which place a hard limit on the total number of FAD sets that can be made in any given period. The analysis indicates that economic gains can be achieved at all levels of the supply chain from the fishing vessel through to the consumer. Highlights: FAD closures cause an economic burden on all parts of the supply chain. FAD set limits can achieve the same environmental outcome. FAD set limits can reduce the economic burden across the supply chain.